Multiplex Platforms for the Identification of Respiratory Pathogens: Are They Useful in Pediatric Clinical Practice? - Esposito, Susanna; Mencacci, Antonella; Cenci, Elio; Camilloni, Barbara; Silvestri, Ettore; Principi, Nicola (Frontiers in Cellular and Infection Microbiology, 2019)
Respiratory tract infections (RTIs) are extremely common especially in the first year of life. Knowledge of the etiology of a RTI is essential to facilitate the appropriate management and the implementation of the most effective control measures. This perspective explains why laboratory methods that can identify pathogens in respiratory secretions have been developed over the course of many years. High-complexity multiplex panel assays that can simultaneously detect up to 20 viruses and up to four bacteria within a few hours have been marketed. However, are these platforms actually useful in pediatric clinical practice? In this manuscript, we showed that these platforms appear to be particularly important for epidemiological studies and clinical research. On the contrary, their routine use in pediatric clinical practice remains debatable. They can be used only in the hospital as they require specific equipment and laboratory technicians with considerable knowledge, training, and experience. Moreover, despite more sensitive and specific than other tests routinely used for respiratory pathogen identification, they do not offer significantly advantage for detection of the true etiology of a respiratory disease. Furthermore, knowledge of which virus is the cause of a respiratory disease is not useful from a therapeutic point of view unless influenza virus or respiratory syncytial virus are the infecting agents as effective drugs are available only for these pathogens. On the other hand, multiplex platforms can be justified in the presence of severe clinical manifestations, and in immunocompromised patients for whom specific treatment option can be available, particularly when they can be used simultaneously with platforms that allow identification of antimicrobial resistance to commonly used drugs. It is highly likely that these platforms, particularly those with high sensitivity and specificity and with low turnaround time, will become essential when new drugs effective and safe against most of the respiratory viruses will be available. Further studies on how to differentiate carriers from patients with true disease, as well as studies on the implications of coinfections and identification of antimicrobial resistance, are warranted.